2020
DOI: 10.22460/infinity.v9i1.p103-110
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Representation of Grade 7 Students in Set Theory Topics Through Problem-Based Learning

Abstract: Set theory has a wide role in mathematical concepts. Students have to understand the set theory before learning other concepts such as algebra and probability. This study aims to determine the effect of the problem-based learning (PBL) model on the students' mathematical representation in set theory topics. The method used in this study is a quasi-experiment design. The populations in this study were 289 students of 7th grade at Secondary School in Palembang. The sample of this study were students of class 7.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Finally, students provide arguments regarding their solutions, showing their efforts to validate and explain the procedures applied in solving the mathematical problem. This is in line with research from Lestari et al (2020), which revealed that mathematical representation is a capability that has to be mastered by students in the learning of mathematics. Overall, students' analyses reflect their efforts to use mathematical symbols, understand pattern relationships, and provide arguments to support their solutions.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, students provide arguments regarding their solutions, showing their efforts to validate and explain the procedures applied in solving the mathematical problem. This is in line with research from Lestari et al (2020), which revealed that mathematical representation is a capability that has to be mastered by students in the learning of mathematics. Overall, students' analyses reflect their efforts to use mathematical symbols, understand pattern relationships, and provide arguments to support their solutions.…”
Section: Discussionsupporting
confidence: 90%
“…Mathematical representation ability is the ability to restate notations, symbols, tables, pictures, graphs, diagrams, equations, or other mathematical expressions into other forms. Mathematical representations consist of visual representations, verbal (written text), mathematical equations, or expressions (Lestari et al, 2020). Representation ability is very important for students to have, with representation ability, can make it easier for students to solve mathematical problems (Sari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical representation is one of the important competencies in learning mathematics. Good representation competency can help students to represent notations, symbols, graphs and other representations in mathematics (Lestari et al, 2020;Muhtarom et al, 2019). All of this will clearly help students when they solve problems.…”
Section: Introductionmentioning
confidence: 99%